A new allele PEL9GG identified by genome-wide association study increases panicle elongation length in rice (Oryza sativa L.) - Dang, Xiaojing; Jing, Chunyu; Zhang, Mengyuan; Li, Xinru; Xu, Qing; Hu, Changmin; Li, Yulong; Zhang, Ying; Wang, Dezheng; Hong, Delin; Jiang, Jianhua (Frontiers in Plant Science, 2023)
Considering the male sterile line has the phenomenon of panicle enclosure, panicle elongation length (PEL) plays an important role in hybrid rice seed production. However, the molecular mechanism underlying this process is poorly understood. In this study, we investigated the PEL phenotypic values of 353 rice accessions across six environments, which shows the abundant phenotypic variation. Combining the 1.3 million single-nucleotide polymorphism, we performed a genome-wide association study on PEL. Three quantitative trait loci (QTL) qPEL4, qPEL6, and qPEL9 were identified significantly associated with PEL, of which qPEL4 and qPEL6 were located in previously reported QTLs and qPEL9 was novel. One causal gene loci PEL9 was identified and validated. The PEL of accessions carrying allele PEL9GG was significantly longer than that of those carrying allele PEL9TT. We also demonstrated that the outcrossing rate of female parents carrying allele PEL9GG increased by 14.81% compared with that of the isogenic line carrying allele PEL9TT in an F1 hybrid seed production field. The allele frequency of PEL9GG increased gradually with an increase in latitude in the Northern Hemisphere. Our results should facilitate the improvement in PEL of female parent of hybrid rice.